2014
DOI: 10.3732/ajb.1300285
|View full text |Cite
|
Sign up to set email alerts
|

Population differentiation for germination and early seedling root growth traits under saline conditions in the annual legume Medicago truncatula (Fabaceae)

Abstract: We report population differentiation for germination and seedling growth traits under saline conditions among populations derived from saline and nonsaline environments. These observations are consistent with a syndrome of adaptations for salinity tolerance during early plant development, including traits that are common among saline environments and those that are idiosyncratic to local populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 85 publications
1
7
0
Order By: Relevance
“…Using the same genotypes of M . truncatula as in the current study, Cordeiro et al [ 34 ] demonstrated that seed germination and timing of germination of non-saline origin populations were negatively influenced by saline environments, while saline origin populations were not affected. These early developmental differences can lead to variation in fitness and population growth rates, and increase the likelihood of parental environmental effects mediating population divergence.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Using the same genotypes of M . truncatula as in the current study, Cordeiro et al [ 34 ] demonstrated that seed germination and timing of germination of non-saline origin populations were negatively influenced by saline environments, while saline origin populations were not affected. These early developmental differences can lead to variation in fitness and population growth rates, and increase the likelihood of parental environmental effects mediating population divergence.…”
Section: Discussionsupporting
confidence: 66%
“…In general, avoidance mechanisms may include seed dormancy or faster plant growth, with both germination and flowering being critical life stages [ 11 , 29 32 ]. Germination is the one of the earliest stages an offspring can experience environmental stress and seeds can either geminate or remain dormant until conditions become more favorable (e.g., [ 33 34 ]). Age at flowering is an important transition stage of the life cycle, and multiple studies on adaptation to stress have demonstrated that selection favors earlier flowering in stressful environments [ 30 , 32 , 35 ], including soil salinity (e.g., [ 23 ]).…”
Section: Introductionmentioning
confidence: 99%
“…However, we find that early germination is correlated with higher growth potential in leaf size (Pearson correlation, r = −0.49, P < 0.0001) and number of leaves (Pearson correlation, r = −0.32, P < 0.0001). A previous study of Tunisian saline adapted genotypes showed that some genotypes exhibit a level of salt tolerance during germination by modulating metabolic and physiological processes to maintain ion balance in the root system [ 83 ] to improve water uptake important for photosynthesis and growth during salinity stress. Overall, we detect parental environmental effects on offspring performance that does not depend on the offspring, where some parental genotypes invest resources into seed size to optimize offspring performance in the next generation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to impaired ABA signaling, AtCPK4 and AtCPK11 mutants are pleiotropic for seedling insensitivity to salt stress and they are impaired in ABA-induced stomatal movement—a process strongly controlled in response to stress. A related experiment found that seedlings of saline origin genotypes from these populations are more sensitive to ABA than non-saline genotypes [ 41 ].…”
Section: Discussionmentioning
confidence: 99%